Menurunkan Intensitas Bullying melalui Metode Role Playing - Baiquniyah Baiquniyah; Arifin Nur Budiono; Siti Rahayu (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2018)
A policy that involves acomponent of students arriving from the head of the school until aparent students .Policy would just go on good if there were concrete steps from school to resuscitate school bullying of all components of how it is very disturbing the teaching and learning process.Then the researcher use a method of role playing which in its implementation resembling guidance of the group to help to drive down the intensity of bullying to their students class VIIIE MTs Nahdlatuth-ThalabahWuluhan in 2017/2018 who are assumed to be quite high .Researchers assume that that method is more efficient because students can directly plays the role of .This study was conducted in the first half of the even on the date may until the date of 2018 04 june 2018. From the results of the pre treatment shows that the intensity of bullying to their students class viii e mtsnahdlatuththalaba in 2017/2018 show range a value sufficiently high 14 from 33 students reached 56-72 value between ,and 17 other students are 40-56 reached midrange set of values,and two students reached susceptible namely 24-40 low,for that researchers planned the act of as many as twice cycles and each cycle three times face to face. Keywords: Role playing, Bullying